1991
DOI: 10.1109/10.81557
|View full text |Cite
|
Sign up to set email alerts
|

Impedance cardiography using band and regional electrodes in supine, sitting, and during exercise

Abstract: The electrical impedance and its first derivative (dZ/dt) were measured at 100 kHz on 10 normal males in supine, sitting, and during upright bicycle exercise in order to compare the contribution of regional electrodes to the standard band electrode signal and to evaluate the possible use of spot electrodes for stroke volume (SV) measurements. Simultaneous measurements were made from band electrodes placed around the neck and lower thorax and from spot electrodes which recorded signals from the neck, upper thor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
23
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 23 publications
3
23
0
Order By: Relevance
“…The third investigation of spot-band comparability was conducted by Patterson, Wang, and Raza (1991). Patterson and colleagues measured Z 0 , dZ/dt peak , and SV during a supine resting condition, a sitting condition, and physical exercise.…”
Section: Cihr Author Manuscriptmentioning
confidence: 99%
See 4 more Smart Citations
“…The third investigation of spot-band comparability was conducted by Patterson, Wang, and Raza (1991). Patterson and colleagues measured Z 0 , dZ/dt peak , and SV during a supine resting condition, a sitting condition, and physical exercise.…”
Section: Cihr Author Manuscriptmentioning
confidence: 99%
“…The authors also evaluated different combinations of spot-band locations and concluded that the dZ/dt waveforms significantly differed among any pairing of spot and/or band combinations. Patterson et al (1991) concluded that placement of electrodes at varying locations resulted in substantial differences in estimates of Z 0 , dZ/dt, and SV.…”
Section: Cihr Author Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations